2005
DOI: 10.1002/jbm.a.30239
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postsurgical tissue adhesion by anti‐inflammatory drug‐loaded pluronic mixtures with sol–gel transition behavior

Abstract: Sol-gel transition temperature-controllable Pluronic F127/F68 mixtures including mildly crosslinked alginate and nonsteroidal anti-inflammatory drug (ibuprofen) were prepared to evaluate their potential as tissue adhesion barrier gels. The sol-gel transition temperatures of the Pluronic mixtures could be controlled by adjusting F127/F68 ratio and polymer concentration. The mildly crosslinked alginate with still flow property provided the residence stability of Pluronic mixture gels in the body. Ibuprofen was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 74 publications
0
76
0
2
Order By: Relevance
“…Poloxamer, a substance composed of nonionic triblock copolymers of the central hydrophobic polypropylene and side hydrophilic polyethylene, is extensively used as a surfactant owing to its amphiphilic feature. Oh et al [33] reported that poloxamer is a good anti-adhesive agent playing the barrier's role appropriately, because it showed fairly good anti-adhesion effects, had small inflammatory reaction and non-toxicity within the body in a study using the peritoneum adhesion model in rats. Reigel et al [34] also said that the substance had about 50% of anti-adhesion effects in an experimental study using the laminectomy model in rabbits, affirming that poloxamer is a useful anti-adhesive agent in spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Poloxamer, a substance composed of nonionic triblock copolymers of the central hydrophobic polypropylene and side hydrophilic polyethylene, is extensively used as a surfactant owing to its amphiphilic feature. Oh et al [33] reported that poloxamer is a good anti-adhesive agent playing the barrier's role appropriately, because it showed fairly good anti-adhesion effects, had small inflammatory reaction and non-toxicity within the body in a study using the peritoneum adhesion model in rats. Reigel et al [34] also said that the substance had about 50% of anti-adhesion effects in an experimental study using the laminectomy model in rabbits, affirming that poloxamer is a useful anti-adhesive agent in spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them need additional fixations to prevent migration. Some of them are very difficult to reposition once placed [7,21,22]. Moreover, it is difficult to cover actively moving 3-dimensional structures such as the heart, graft vessels, and coronary bypass grafts with film type barriers.…”
Section: Discussionmentioning
confidence: 99%
“…However, they flow to the dependant portion and can be drained too early by a drainage catheter before they can prevent adhesion formation [22]. Thus, the viscosity of the solution type barrier is an important factor in the clinical field.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were seeded onto 90-mm tissue culture dishes and grown to 80% confluence, then used for ERK1/2 (Cell Signaling, USA), SMAD2/3 (Cell Signaling), collagen (Santa Cruz Biotechnology, Santa Cruz, CA, USA), and cell proliferation assays. 4 /ml) were seeded in 96-well culture plates. NIH/3T3 cells, with and without stimulation by FGF-2, were treated with increasing Celecoxib suppresses fibroblast proliferation and collagen expression by inhibiting ERK1/2 and SMAD2/3 phosphorylation concentrations of celecoxib.…”
Section: Methodsmentioning
confidence: 99%
“…Certain selective and nonselective cyclooxygenase-2 enzyme (COX-2) inhibitors have been shown to inhibit adhesion formation, but have rarely been applied clinically due to their limited effect (4)(5)(6)(7)(8)(9)(10). Celecoxib, a selective COX-2 inhibitor, has been shown to produce a maximal reduction in intra-abdominal adhesion formation in comparison to rofecoxib and nonselective COX-2 inhibitors, and therefore provides a promising therapy for all types of adhesions (11,12).…”
Section: Introductionmentioning
confidence: 99%